Sistem Asosiasi Penyusunan Obat Pada Apotek Balai Rehabilitasi Badan Narkotika Nasional Baddoka Menggunakan Algoritma Apriori - Tatik Maslihatin (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2020)
Abstract. This research was conducted to implement a priori algorithm in drug association. The research method used is descriptive. The results of this study indicate that the drug association application can provide drug associations in accordance with calculations carried out manually based on the results of the a priori algorithm testing minimum support 3 and minimum confidence 3 showing that the results obtained are the same, with an accuracy level of 90 -98. %. So that it can be used in determining drug associations based on drugs that are often used simultaneously.